Non-accidental non-fatal poisonings attended by emergency ambulance crews: an observational study of data sources and epidemiology. Issue 8 (18th August 2016) - John, Ann; Okolie, Chukwudi; Porter, Alison; Moore, Chris; Thomas, Gareth; Whitfield, Richard; Oretti, Rossana; Snooks, Helen
Abstract : Background: Non-accidental non-fatal poisoning (NANFP) is associated with high risk of repeat episodes and fatality. This cross-sectional study aims to describe the data sources and epidemiology of non-fatal poisonings (NFPs) presenting to the emergency ambulance service. Methods: We assessed incidents of NFP across Wales from electronic ambulance call centre records and paper records completed by attending ambulance crews, December 2007 to February 2008. We descriptively analysed data completed by attending crews. Results: 92 331 calls were made to the ambulance call centre, of which 3923 (4.2%) were coded as 'overdose' or 'poisoning'. During the same period, ambulance crews recorded 1827 attended NANFP incidents in those categories, of which 1287 (70.4%) had been identified in the call centre. 76.1% (1356/1782) were aged 15–44 years and 54.2% (991/1827) were female. 75.0% (1302/1753) of incidents occurred in areas from the lower 2 quintiles of deprivation in Wales. Substance taken was reported in 90% of cases (n=1639). Multiple ingestion was common (n=886, 54.1%). Psychotropic was the most frequently taken group of substances (n=585, 32.0%) and paracetamol (n=484, 26.5%) was the most frequently taken substance prehospital. Almost half of patients had taken alcohol alongside other substances (n=844, 46.2%). Naloxone was the most frequently administered treatment (n=137, 7.5%). Only 142/1827 (7.8%) patients were not transported to hospital, of whom 4 were recorded to have been given naloxone. Conclusions: We report new data on the epidemiology of NFP across substance types at national level, highlighting deficiencies in information systems and high levels of multiple ingestion. In order to develop policy and practice for this patient group prehospital and further along the care pathway, information systems need to be developed to allow accurate routine monitoring of volume, presentation and outcomes.